EVALUATION OF ANTIMUTAGENIC AND ANTIOXIDANT ACTIVITIES OF RUTIN - RAJINDER KAUR,; SAROJ ARORA,; A.K. THUKRAL, (International Journal of Pharma and Bio Sciences, 2015)
Rutin is a phenolic compound and found in many plant species. Its name is derived from Ruta graveolens a plant that contain this compound. Rutin has many health benefits like it inhibits platelet aggregation, inflammation, hemorrhoid development etc. It is also used in dietary supplements of human beings for its health benefits. Therefore, this study was planned to investigate its other medicinal uses i.e. antimutagenic and antioxidant activities. The antimutagenic activity of rutin was checked by using plate incorporation assay or Ames assay. Antioxidant potential was determined through various in vitro assays like DPPH free radical scavenging assay, lipid peroxidation, deoxyribose degradation (site-specific and non-site specific methods), reducing power, and chelating power assays. In both antimutagenic and antioxidant assays, rutin exhibited potent free radical scavenging and mutation inhibitory effects. This research paper is a part of my Ph.D. work.